Ekonomi Syariah dan Dampaknya di Indonesia: Kontribusi terhadap Pembangunan Berkelanjutan - Indrawati, Peni (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2024)
Sharia economy, based on Islamic principles such as fairness, transparency, and prohibition of usury, has become an important pillar in Indonesia's economic development. This study analyzes the impact of sharia economy on economic growth, financial inclusion, and the achievement of Sustainable Development Goals (SDGs) in Indonesia. Using a qualitative approach based on a literature review of 20 Scopus-indexed articles, this study explores how sharia economy supports sustainable development through financial instruments such as green sukuk, zakat, and productive waqf, as well as the integration of technologies such as FinTech and blockchain. The results show that sharia economy increases financial access for underserved communities, reduces poverty (SDG 1), promotes inclusive economic growth (SDG 8), and supports environmental sustainability (SDG 13). However, challenges such as low sharia financial literacy, suboptimal regulations, and the digital divide still hinder its full potential. This study recommends strengthening regulations, improving financial literacy, adopting technology, and multi-stakeholder collaboration to accelerate the impact of sharia economy in Indonesia.